An inference-based bootstrap and mixed methods approach to examining the impacts of behavior-based safety on job satisfaction and stress: from the construction workers’ perception - Saedi, Ali Mohammad; Zaidi Isa,; Siti Sarah Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Behaviour-Based Safety programme requires diligent support, adequate planning, and sufficient resources, in addition to exceptional motivations. This study aimed to identify possible elements that reflect an individual's perception of BBS and its influence on job satisfaction and stress. In order to identify critical factors influencing employees' perceptions of BBS in construction industry, a series of individual semi-structured interviews were conducted with experts (n = 12). Partial Least Squares (PLS-SEM) was used to analyse the effect of BBS perception on employee work stress and job satisfaction at five construction sites utilising BBS in Malaysia. The study identified seven factors that influence employees' perception of BBS. It also indicated that employees' work stress and job satisfaction are directly affected by how they perceive BBS. Therefore, an improved BBS can help employees differentiate between safe and unsafe behaviours, hereby enhancing prevention of accidents, job satisfaction, welfare, and the overall safety culture of the organisation.